Evaluasi Kinerja Ekonomi Keuangan Dengan Menggunakan Metode Value For Money Pada Badan Keuangan dan Aset Daerah Kota Medan - Muhammad Syahbudi; Rizky Febrian Saragih (Journal Of Business, Finance, and Economics (JBFE), 2022)
The goals of this study are to: (1) analyze the day-to-day operations of the Bank for Foreign Exchange in Kota Medan; and (2) determine if the procedures for opening bank accounts there comply with the rules governing pending transactions. (1) Value for money-focused banking work at BPK Kota Medan is very good and adheres to three principles: efficacy, effectiveness, and warning; and (2) Opening a bank account at the BPK Kota Medan. This means that business initiatives must be carried out in a way that maximizes financial resources and is especially focused on the needs of the general populace or the local populace.